2018
DOI: 10.1080/1343943x.2018.1541712
|View full text |Cite
|
Sign up to set email alerts
|

Variability and estimating in fruiting of shea tree (Vitellaria paradoxaC.F. Gaertn) associated to climatic conditions in West Africa: implications for sustainable management and development

Abstract: Shea tree (Vitellaria paradoxa) is one of the main native oil plants with high economic value in Africa. Its fruits are used for food, medicinal, cultural and exportation purposes. However, the lack of efficient tools to assess annual fruit production of the species limits the sustainable management of its resources. Therefore, production statistics are useful to organize the activities of the shea sector. This study aimed to (i) assess the interannual variation in fruit production along a climatic gradient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The impacts of climate on the expression of morphological characters have also been reported in Northern Equator (Maranz and Wiesman, 2003), Mali (Sanou et al, 2006;Tchabi and Adechi, 2014), Benin (Kougblénou et al, 2012;Kafilatou et al, 2015) and Uganda (Gwali et al, 2012). Moreover, in area of study the mineral composition of the soil, varying from one ecological zone to another, would have also influenced the expression of morphological characters as reported by Sanou et al (2006), Moore (2008) and Bondé et al (2019) respectively in studies on the vegetative characteristics of shea tree parks in Mali, Eastern Ghana and West Africa. The environmental effect significantly influencing the expression of agromorphological characters in shea tree can lead to a possible structuring of elite shea trees according to districts or departments.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The impacts of climate on the expression of morphological characters have also been reported in Northern Equator (Maranz and Wiesman, 2003), Mali (Sanou et al, 2006;Tchabi and Adechi, 2014), Benin (Kougblénou et al, 2012;Kafilatou et al, 2015) and Uganda (Gwali et al, 2012). Moreover, in area of study the mineral composition of the soil, varying from one ecological zone to another, would have also influenced the expression of morphological characters as reported by Sanou et al (2006), Moore (2008) and Bondé et al (2019) respectively in studies on the vegetative characteristics of shea tree parks in Mali, Eastern Ghana and West Africa. The environmental effect significantly influencing the expression of agromorphological characters in shea tree can lead to a possible structuring of elite shea trees according to districts or departments.…”
Section: Discussionmentioning
confidence: 75%
“…To overcome these problems, progressive domestication and genetic improvement of the species are being considered. Previous research has focused on fruit production (Lamien, 2006;Aleza et al, 2018), vegetative propagation (Bonkoungou et al, 1988), molecular diversity of populations (Bouvet et al, 2004;Fontaine et al, 2004;Sanou et al, 2005;Gwali et al, 2014 ;Abdulai et al, 2016), the spatial structure of populations (Kelly et al, 2004;Sanou et al, 2006, Aleza et al, 2015, the parasitism of the shea trees (Bayala et al, 2009;Samaké et al, 2011), the variability of fruit yields (Lamien et al, 2007;Bondé et al, 2019), etc. In Côte d'Ivoire especially, researches on V. paradoxa by Salé et al (1991) reported that some characters such as fruit number, leaf and fruit size, leaf density, flowering and fruit ripening times are related to nut and butter yields.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit production was visually measured by counting the number of fruits on the fruiting branches. The total number of fruits per tree was assessed according to the method developed by Bondé et al (). The effect of the competition on the fruit production of shea tree was appreciated in comparison with the density of adult trees growing around each sampled tree.…”
Section: Methodsmentioning
confidence: 99%
“…Studies conducted at local scale showed that the performance in fruit production of shea tree is significantly affected by land use and soil types (Aleza, Villamor, Nyarko, Wala, & Akpagana, ; Lamien, Ouédraogo, Diallo, & Guinko, ). Previous studies in West Africa reported that climatic gradient has an effect on the species’ fruit production with the highest production in Sudanian zone (Bondé, Ouédraogo, Ouédraogo, Thiombiano, & Boussim, ; Glèle Kakaï et al, ). A significant interannual variation in fruit production of shea tree was also observed by Boffa et al (), Soro, Koffi, and Soro () and Bondé et al ().…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation